Simple Workflow Changes Enable Effective Patient Identity Matching in Poison Control - Cummins, Mollie R.; Ranade-Kharkar, Pallavi; Johansen, Cody; Bennett, Heather; Gabriel, Shelley; Crouch, Barbara I.; Del Fiol, Guilherme; Hoffman, Matt (Applied Clinical Informatics, 2018)
Background U.S. poison control centers pose a special case for patient identity matching because they collect only minimal patient identifying information.Methods In early 2017, the Utah Poison Control Center (Utah PCC) initiated participation in regional health information exchange by sending Health Level Seven Consolidated Clinical Document Architecture (C-CDA) documents to the Utah Health Information Network and Intermountain Healthcare. To increase the documentation of patient identifiers by the Utah PCC, we (1) adapted documentation practices to enable more complete and consistent documentation, and (2) implemented staff training to improve collection of identifiers.Results Compared with the same time period in 2016, the Utah PCC showed an increase of 27% (p < 0.001) in collection of birth date for cases referred to a health care facility, while improvements in the collection of other identifiers ranged from 0 to 8%. Automated patient identity matching was successful for 77% (100 of 130) of the C-CDAs.Conclusion Historical processes and procedures for matching patient identities require adaptation or added functionality to adequately support the PCC use case.
Keywords: health information exchange; toxicology; delivery of health care; electronic health records